Preparation and properties of foamed cellulose acetate/polylactic acid blends. Issue 12 (5th October 2021) - Zhang, Chenghao; Wan, Lei; Gu, Han; Hu, Qipeng; Ding, Yajun; Ying, Sanjiu
Abstract: In order to improve the foaming performance of pure cellulose acetate (CA), blends were prepared by mixing polylactic acid (PLA) in CA and foamed by supercritical CO2 (ScCO2 ) in this study. The effect of PLA content (percentage by mass of blend) on structure, thermal properties, rheological properties, foaming properties and mechanical properties of the blends was investigated. The results showed that the addition of PLA destroyed the original hydrogen bonds of CA, while the blends had good crystallization properties. At the same time, compared with pure CA, the glass transition temperature ( T g ) of the blends decreased, and the initial decomposition temperature ( T 0 ) was reduced from 349.41°C (pure CA) to 334.68°C (CA/20%PLA). In addition, the rheological properties of the blends were improved, and the viscosity was reduced, which was obviously beneficial to foaming process. The pore size and density of the foamed blends both reached the maximum value at 20%PLA. The presence of PLA could degrade the mechanical properties of the blends. However, the overall drop (1.01 KJ/m 2 ) of impact strength of the blends after foaming is much smaller than that before foaming (12.11 KJ/m 2 ), indicating that the improvement of foaming performance was beneficial to improve its impact strength. Abstract : Polymer foams with microporous structure were prepared from cellulose acetate (CA)/polylactic acid (PLA) blends with CO2 as a foaming agent. The results showed that the addition of PLA significantly improved the foaming performance of CA.